1999
DOI: 10.1176/ajp.156.6.912
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Psychotraumatic Properties of a Cardiac Arrest Experience

Abstract: This study provides the first empirical evidence that the application of the posttraumatic stress disorder paradigm in the long-term evaluation of cardiac arrest survivors significantly contributes to defining a patient population at high risk for serious emotional disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 43 publications
2
42
1
4
Order By: Relevance
“…One prospective cohort study (LOE P1), 666 1 "follow-up of untreated control group in an RCT" study (LOE P2), 667 3 retrospective cohort studies (LOE P3), 634,668,669 and 12 case series (LOE P4) 417,670 -680 showed that cardiac arrest survivors experience problems in physical, cognitive, psychological, and social functioning that impact on quality of life to a varying degree.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…One prospective cohort study (LOE P1), 666 1 "follow-up of untreated control group in an RCT" study (LOE P2), 667 3 retrospective cohort studies (LOE P3), 634,668,669 and 12 case series (LOE P4) 417,670 -680 showed that cardiac arrest survivors experience problems in physical, cognitive, psychological, and social functioning that impact on quality of life to a varying degree.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…The prevalence rate varied from 19% (30) to 38% (31); 19% was found in a study that assessed PTSD close to the index event (mean 9.6 months [range 3-18 months]) (30), whereas studies evaluating PTSD caseness Ͼ22 months found prevalence rates of 27% (32) and 38% (31). Although 3 studies found prevalence rates of a considerable magnitude, a case-control study looking at the risk of PTSD within various patient groups (extensive burns, spinal disorders, amputations, major chest trauma, heart failure, and cardiac arrest) did not identify SCA as a risk factor for PTSD (33).…”
Section: Scamentioning
confidence: 99%
“…Psychosocial outcomes have been widely investigated in health conditions, including neurological and cardiac disorders, however the psychosocial outcomes of ABI following CA is an under-researched area, with much of the psychological research concentrating on cognitive outcomes.9, 10 The limited existing research has provided variable findings; however there are suggestions that individuals have lower quality of life (QOL) when compared to the general population.11-13 Survivors of CA with ABI have also been found to experience psychological difficulties including anxiety, 14 depression 14,15 and post-traumatic stress disorder (PTSD) symptoms. 14,16 Difficulties with social functioning 14,17 have also been identified.…”
Section: Introductionmentioning
confidence: 99%